Mobile information hub and services - Zhang, Yuhao (2017)
Over the last decade, smartphones with high-resolution cameras, hardware-accelerated graphics, and broadband wireless networks have evolved into powerful mobile information hubs where new technologies can be integrated to provide various services. The adoption of 3D graphics technology enables smartphones to communicate information in a more intelligent way. It brings at the forefront of which is Mobile Visual Search (MVS), a technology that provides various services based on image search. The objective of this project was to modify and employ a MVS system (developed by previous FYP students) on an Android platform and to produce 3D graphics of the search results on the phone screen. It incorporated Open Source Graphics Library (OpenGL) functions into the system and implemented user interactions such as rotating, scaling and changing the appearance of the 3D model. At the end of the development phase, the system was successfully integrated. Tests were conducted to evaluate the performance of the integrated system on a Samsung Galaxy S3 smartphone. The server database contained 5 model OBJ files with a distractor set of 1,000 images. The tests showed an average rendering time of 96.1 seconds for a model with an OBJ data size of 200 KB.